Ligand Structure Determines Nanoparticles' Atomic Structure, Metal-Ligand Interface and Properties - Rambukwella, Milan; Sakthivel, Naga Arjun; Delcamp, Jared H.; Sementa, Luca; Fortunelli, Alessandro; Dass, Amala (Frontiers in Chemistry, 2018)
The nature of the ligands dictates the composition, molecular formulae, atomic structure and the physical properties of thiolate protected gold nanomolecules, Aun(SR)y. In this review, we describe the ligand effect for three classes of thiols namely, aliphatic, AL or aliphatic-like, aromatic, AR, or bulky, BU thiol ligands. The ligand effect is demonstrated using three experimental setups namely: (1) The nanomolecule series obtained by direct synthesis using AL, AR, and BU ligands; (2) Molecular conversion and interconversion between Au38(S-AL)24, Au36(S-AR)24, and Au30(S-BU)18 nanomolecules such as Au38(S-AL)24, Au36(S-AR)24, and Au30(S-BU)18; and (3) Synthesis of Au38, Au36, and Au30 nanomolecules from one precursor Aun(S-glutathione)m upon reacting with AL, AR and BU ligands. These nanomolecules possess unique geometric core structure, metal-ligand staple interface, optical and electrochemical properties. The results unequivocally demonstrate that the ligand structure determines the nanomolecules’ atomic structure, metal-ligand interface and properties. The direct synthesis approach reveals that AL, AR, and BU ligands form nanomolecules with unique atomic structure and composition. Similarly, the nature of the ligand plays a pivotal role and has a significant impact on the passivated systems such as metal nanoparticles, quantum dots, magnetic nanoparticles and self-assembled monolayers (SAMs). Computational analysis demonstrates and predicts the thermodynamic stability of gold nanomolecules and the importance of ligand-ligand interactions that clearly stands out as a determining factor, especially for species with AL ligands such as Au38(S-AL)24.